Certified Nursing Aides' Training Hours and COVID Case and Mortality Rates Across States in the U.S.: Implications for Infection Prevention and Control and Relationships With Nursing Home Residents - Lené Levy-Storms; Lené Levy-Storms; Amelia Mueller-Williams (Frontiers Media S.A., 2022)
Disproportionately high COVID case and mortality rates in skilled nursing facilities (SNFs) have heightened interest in the role of Certified Nursing Aides (CNAs) in the care of residents living in SNFs. This policy brief will make recommendations for CNA training based on an examination of two sources of secondary data using descriptive statistics. From the first source of secondary data, 34% of CNAs report feeling inadequately trained. The second source, U.S. government data, revealed statistically significant negative correlations between the amount of CNA training required across states and COVID mortality rates (Kendall's τb = −0.32; p = 0.002) but not case rates (Kendall's τb = −0.18; p = 0.09). More training for CNAs may not only reduce health risks from infectious diseases but also improve how they relate to SNF residents during care.